2007
DOI: 10.1021/jf063287d
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Enzyme-Linked Immunosorbent Assay for the Detection of Pentachloronitrobenzene Residues in Environmental Samples

Abstract: A competitive enzyme-linked immunosorbent assay (ELISA) for pentachloronitrobenzene (PCNB), a fungicide and chemical intermediate, was developed using a polyclonal antiserum produced against a hapten-protein conjugate of pentachlorophenoxypropionic acid-bovine serum albumin (BSA). An indirect competitive ELISA of PCNB showed an IC50 of 37 ng/mL and a limit of detection (LOD) of 7 ng/mL. The ELISA can tolerate up to 10% (v/v) methanol, 5% (v/v) acetonitrile, or 5% (v/v) acetone without significant fluctuation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Accordingly, we studied organic solvent, pH, ionic strength, detergent, and blocking reagent as possible sources of interference in the ELISA with DBP MAb. Most researchers reached the same conclusion that methanol caused the least negative effect on the ELISA performance [33][35]. However, our assays showed that DMF presented the best combination of A max and IC 50 .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Accordingly, we studied organic solvent, pH, ionic strength, detergent, and blocking reagent as possible sources of interference in the ELISA with DBP MAb. Most researchers reached the same conclusion that methanol caused the least negative effect on the ELISA performance [33][35]. However, our assays showed that DMF presented the best combination of A max and IC 50 .…”
Section: Discussionsupporting
confidence: 70%
“…The ELISA for DBP was very sensitive to ionic strength, that is, A max and IC 50 values significantly decreased at high concentration of NaCl. The sensitivity improvement by increased ionic strength may be due to dispersion and weakening of the nonspecific binding derived from antibody [35]. Tween-20 is a nonionic detergent commonly used in washing buffer to reduce nonspecific interactions in ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunization was done according to the protocol reported previously. 38 Each immunogen of BSA-P1 and BSA-P5 was injected into two female New Zealand white rabbits. The animals were bled around 3 months following the first immunization.…”
Section: Immunization Protocolmentioning
confidence: 99%
“…For all the tested compounds, the cross reactivity values achieved were very low (52.5%) except for 2,3,4,6-tetrachlorophenol (5.6%) and 2,3,5,6-tetrachlorophenol (9.2%). The sensitivity and cross-reactivity of antibodies are related to the structure of immunizing haptens, coating antigen used, and physicochemical properties of ligand, including the minimum energy, threedimensional shape, electrostatic interaction, hydrophobic interaction, hydrogen bond (Xu et al 2007). The computational modeling may provide information useful in understanding cross reactivity.…”
Section: Antisera Specificitymentioning
confidence: 99%